The Smoke That Transforms, New Looks to Understand the Ritual Tecnology O the Pipes of Atacama Salt Lake; [el Humo Que Transforma, Nuevas Miradas Para Entender la Tecnología Ritual de Las Pipas del Salar de Atacama] - Echeverria-Morgado, J (Universidad de Tarapaca, 2023)
This proposal provides new insights into the archaeological pipes of the Salar de Atacama, seeking to complement the hypotheses that place them as an initial link of psychotropic consumption in the South Andes. Thus, pipes are addressed regarding their possibility of burning fume-emanating substances. Fumes are an essential ingredient in secular practices and indigenous rituals that have remained within the communities of the Salar de Atacama and Andean peoples. A study of traces of use, trajectories, and life histories of archaeological specimens, added to an exercise in experimental archaeology and ethnographic fieldwork, are lines of evidence that allow us to sketch a repertoire linked to these objects and their use in pre-Hispanic times. © 2023, Universidad de Tarapaca. All rights reserved.